Kidney Transplantation in Older Adults: Does Age Affect Graft Survival? - Ahmadnia, Hassan; Shamsa, Ali; Yarmohammadi, Aliasghar; Darabi, Mohammadreza; Asl Zare, Mohammad Asl Zare (Urology Journal, 2009)
Introduction: There is a paucity of data on long-term patient and graft survival in the older kidney recipients. Our aim was to evaluate the long-term outcomes of kidney transplantation in patients aged 50 years and older and compare them with outcomes in younger recipients. Materials and Methods: Forty-seven recipients aged 50 years and older and 47 recipients aged younger than 50 years were randomly assigned to two groups (groups 1 and 2, respectively). Patients who had received a cadaveric kidney allograft were excluded from the study. Data including demographic and clinical characteristics, early complications, early mortality, and actuarial patient and graft survival rates were collected, and the two groups were compared, accordingly.Â  Results: The rates of early complications and mortality were not different between the two groups. Patient survival rates at 1, 3, 5, and 7 years were 72%, 58%, 41%, and 41% for patients in group 1 and 95%, 86%, 86%, and 86% for patients in group 2, respectively (P = 0.007). Graft survival rates were 72%, 58%, 41%, and 41% for patients in group 1 and 95%, 85%, 85%, and 85% for patients in group 2, respectively (P = 0.006). Graft loss due to patient death was 33.33% in group 1 compared with 4.25% in group 2 (P < 0.001). Conclusion: Kidney transplantation should be considered in patients older than 50 years, since the graft survival rate is acceptable in this population, and early mortality and complications in this group are not different than those of younger recipients. Although older patients have a shorter life expectancy, they benefit from renal transplantation in ways similar to younger kidney transplant recipients.